Sustainable Supply Chain Management in Smart City Design: A Case Study of Al Khobar City Centre - Hany Hossam Eldien; Karim Gazzeh; Emad Hammad (International Journal of Supply Chain Management, 2020)
Abstract—The purpose of this study is to analyze the impact of supply chain management (SCM) on smart city development. More specifically, we investigate the connections between smart cities, and supply network characteristics (supply network structure and governance mechanisms). Urban spaces, which have high acoustic quality, are a rare resource that must be protected to achieve the sustainable urban development as well as health and comfort of the urban space users. Urban morphology and urban environment are major topics for various urban studies using multiple approaches. Many of these approaches focus firstly on the visual analysis of urban area, while a shortage of urban sound quality studies can be highlighted. In this study, we propose the sound-walk procedure to evaluate the urban supply chain managements in Khobar city center. This work aims to understand how the use of supply chain management concept can help in environmental issues in urban areas. The relationships between smart cities, big data and supply networks cannot be described simply by using a linear, cause-and-effect framework. Accordingly, we have proposed an integrative framework that can be used in future empirical studies to analyze smart cities and big data implications on SCM. This will allow city-users and planners to determine and identify the urban supply chain management, and suggest that a decrease of noise level is not the only way to improve the urban environment.